Ideologi dan Strategi Gerakan Filantropi Islam: Studi Kasus Hilal Merah Indonesia - Fahlesa Munabari (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2021)
This article discusses the emergence, activities, and the ways in which Hilal Merah Indonesia (HILMI) mobilizes its resources. HILMI is the autonomous philanthropic division of Front Pembela Islam (FPI) whose activities are focused on delivering humanitarian assistance to beneficiaries ranging from those suffering from natural disasters to those living in severe poverty. A growing body of literature has investigated faith-based organizations that provide humanitarian services in Indonesia such as Dompet Dhuafa, Muhammadiyah (Lazismu), as well as Nahdlatul Ulama’s (Lazisnu). However, little attention has been paid to the social and humanitarian activities of Islamic radical movements in the country, such as the FPI. This article aims to address this literature gap. It used a case study approach to obtain primary data as well as a comprehensive understanding of HILMI. The primary data collection was carried out through field observations which were mostly carried out at the HILMI secretariat office in the Kalibata area, South Jakarta, DKI Jakarta. Interviews were conducted with key HILMI informants and a number of FPI officials. This study also used secondary data such as scholarly literature and news articles. The article opens up with the genesis and resource mobilization strategy of FPI. Through the lens of social movement theory, it then analyzes the emergence and resource mobilization strategy of HILMI. It demonstrates how the informal, loose, and flexible structure and culture of its parent organization, FPI, is reflected in the ways in which HILMI engages in the provision of humanitarian assistance in the country.